(untitled) (Federal University Gusau Faculty of Education Journal, 2025)
This study assessed the role of information and communication technology (ICT) in improving administrative effectiveness in public secondary schools in Edo South Senatorial District of Edo State. The study specifically examined how ICT influences supervision, discipline management, record-keeping, and decision-making among school administrators. A descriptive survey research design was adopted. The population comprised all teachers and principals in public secondary schools in Edo South, totaling 2,412 personnel across 135 schools. A sample of 220 respondents was selected using a multi-stage random sampling technique. Data were collected using a structured questionnaire titled ICT and Administrative Effectiveness Questionnaire (ICTAEQ) and supported by official school records. The reliability of the instrument was established through Cronbach’s Alpha, which yielded 0.92. Data were analyzed using descriptive statistics (frequency, mean, and standard deviation) and inferential statistics (Pearson correlation, regression, t-test, and ANOVA) at a 0.05 level of significance. Findings revealed that ICT significantly improved supervision practices (r = 0.471, p < 0.05), enhanced record-keeping efficiency (r = 0.458, p < 0.05), and strengthened discipline management (r = 0.439, p < 0.05). Regression results further showed that ICT usage jointly predicted 41% of the variance in administrative effectiveness. Based on the findings, it was concluded that ICT plays a vital role in enhancing school administration in Edo South. The study recommended the provision of adequate ICT facilities in schools, regular training for principals and teachers on ICT tools, and the integration of digital record systems in school management.